Brittle cornea, blue sclera, and red hair syndrome (the brittle cornea syndrome). Issue 3 (March 1980) - Ticho, U; Ivry, M; Merin, S
Abstract : A syndrome of red hair, blue sclera, and brittle cornea with recurrent spontaneous perforations is presented in 2 siblings of a Tunisian Jewish family. The genetic transmission of this disorder is autosomal recessive. This is the second description of this syndrome, which should be called the 'brittle cornea syndrome'. This syndrome has so far been reported only in Tunisian Jewish families.